Survival of a highly toxic dose of caffeine. (8th February 2013) - Bioh, Gabriel; Gallagher, Mark M; Prasad, Usha
Abstract : A 27-year-old woman with a history of depression and previous overdose presented within 60 min of ingestion of 50 g of caffeine powder. Initially alert but hypotensive and tachycardic, the patient developed a broad complex tachycardia followed by a seizure and multiple ventricular fibrillation (VF) arrests. Following multiple defibrillations for VF, eight cycles of cardiopulmonary resuscitation and treatment with amiodarone, lidocaine, magnesium and potassium supplementation, the patient went to the intensive care unit (ICU). While there, the patient had further VF and required haemofiltration for a profound metabolic acidaemia with cardiac rhythm instability. She developed a postcardiac arrest systemic inflammatory response syndrome with episodes of acute pulmonary oedema, profound vasoplegia, hypothermia and coagulopathy. After 5 days in the ICU, the patient was stable enough to be transferred to the ward, with a persistent sinus tachycardia, and was discharged 3 days later with cardiology and psychiatry follow-up.